Antiobesity potential of major metabolites from Clitoria ternatea kombucha: Untargeted metabolomic profiling and molecular docking simulations - Hardinsyah Hardinsyah; William Ben Gunawan; Fahrul Nurkolis; Darmawan Alisaputra; Rudy Kurniawan; Nelly Mayulu; Nurpudji Astuti Taslim; Trina Ekawati Tallei (Current Research in Food Science, 2023)
The prevalence of obesity is rapidly increasing and poses serious health risks accompanied by a decrease in life expectancy and quality of life. Therefore, the therapeutic potential of natural-derived nutraceuticals against obesity and its comorbidities needs to be explored. Molecular inhibition of lipase enzymes and fat mass and obesity-associated (FTO) protein has attracted some recent interest in efforts to find antiobesity agents. This study aims to innovate a fermented drink from Clitoria ternatea kombucha (CTK), find out their metabolites profile, and determine the antiobesity potential through a molecular docking study. The CTK formulation refers to previous research while the metabolites profile was determined using HPLC-ESI-HRMS/MS. Major compounds were selected based on best match value > 99.0% of the M/Z cloud database. A total of 79 compounds were identified in CTK, and 13 ideal compounds were selected to be simulated in the molecular docking study against human pancreatic lipase, α-amylase, α-glucosidase, porcine pancreatic lipase, and FTO proteins. The study found that Kaempferol, Quercetin-3β-D-glucoside, Quercetin, Dibenzylamine, and α-Pyrrolidinopropiophenone showed the best potential as functional antiobesity compounds since their affinity value ranked high in each respective receptor. In conclusion, the major compounds of CTK metabolites have the potential to be promising functional foods against obesity. However, further in vitro and in vivo studies should validate these health benefits.